2014
DOI: 10.1371/journal.pone.0091303
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Alleviates Neuropathic Pain by Inhibiting p300/CBP Histone Acetyltransferase Activity-Regulated Expression of BDNF and Cox-2 in a Rat Model

Abstract: The management of neuropathic pain is still a major challenge because of its unresponsiveness to most common treatments. Curcumin has been reported to play an active role in the treatment of various neurological disorders, such as neuropathic pain. Curcumin has long been recognized as a p300/CREB-binding protein (CBP) inhibitor of histone acetyltransferase (HAT) activity. However, this mechanism has never been investigated for the treatment of neuropathic pain with curcumin. The aim of the present study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(86 citation statements)
references
References 68 publications
3
81
0
1
Order By: Relevance
“…Moreover, disruption of this interaction deregulates the NF-κB pathway by interfering with its negative feedback loop. Another recent study also showed that treatment with 60 mg/kg of curcumin increased the mechanical threshold, as in your study, and reduced COX-2 gene expression [5]. That study revealed that curcumin treatment downregulated the recruitment and altered the binding of protein p300/CBP at the BDNF and COX-2 promoters.…”
supporting
confidence: 62%
“…Moreover, disruption of this interaction deregulates the NF-κB pathway by interfering with its negative feedback loop. Another recent study also showed that treatment with 60 mg/kg of curcumin increased the mechanical threshold, as in your study, and reduced COX-2 gene expression [5]. That study revealed that curcumin treatment downregulated the recruitment and altered the binding of protein p300/CBP at the BDNF and COX-2 promoters.…”
supporting
confidence: 62%
“…52) In addition, it has been reported that there is an enhancement in histone acetyltransferase (HAT) activity at the time of neuropathic pain. 53) A possible mechanism underlying the increased expression of UGT2B can be proposed based on these reports. Namely, since histone acetylation was enhanced in the promoter region of UGT2B in the liver and the ability to bind to the response sequence of PXR increased, it is thought that the expression of UGT was enhanced without an increase in the nuclear translocation of PXR.…”
Section: Fig 4 Amount Of Pxr Transported To the Nucleus Of Mice Witmentioning
confidence: 94%
“…Polymorphism study by Jeon et al described the association of miR-146a, miR-149, miR-196a2, and miR-499 with cerebral ischemia stroke and silent brain infarction risk (Jeon et al 2013). Likewise, the study by Zhu et al described the correlation of miR-124 with neuronal death during ischemia/Reperfusion by regulating Ku 70 expression (Zhu et al 2014). Khanna et al described the loss of miR29b with neuronal cell death during stroke (Khanna et al 2013), and Pandi et al showed down-regulation of miR-29c in de-repression of DNMT 3a during ischemic brain damage (Pandi et al 2013).…”
Section: Epigenetic Impact Of Curcuminmentioning
confidence: 98%
“…Besides acting on HDAC, curcumin also inhibit HAT. Zhu et al (2014) have determined that curcumin alleviates neuropathic pain by inhibiting p300/CREB-binding protein (CBP) of histone acetyltransferase (HAT) activity and regulating the expression of BDNF as well as cox-2 in rat. Kang et al (2006) have shown that HAT inhibition by curcumin enhanced Caspase-3-dependent Glioma Cell Death and Neurogenesis of Neural Progenitor Cells.…”
Section: Epigenetic Impact Of Curcuminmentioning
confidence: 99%